263 Pleiotropic effects of IL-7 in prostate cancer patients receiving Sipuleucel-T vaccination. (10th December 2020) - Duault, Caroline; Ramchurren, Nirasha; Pachynski, Russell; Fong, Lawrence; Bendall, Sean; Pichavant, Mina; Sahaf, Bita; Morishima, Chihiro; D'Amico, Leonard; Cheever, Martin; Fling, Steven; Maecker, Holden
Abstract : Background: Sipuleucel-T (Provenge) is the first therapeutic vaccination approved by the FDA so far, indicated for advanced metastatic prostate cancer patients. Despite an improvement of the overall survival, the benefits of the therapy are still short-term so increasing the duration of the efficacy is necessary. Specifically, T-cell anergy is one of the challenges that we need to overcome to improve the overall efficacy. IL-7 is known to promote the naive T cell activation and to increase the proliferation and activation of the T cell memory subsets. Therefore, in this phase II clinical trial, we tested the therapeutic potential of a human recombinant glycosylated IL-7 after completion of the Provenge therapy on asymptomatic advanced prostate cancer patients. Methods: To get a comprehensive analysis of the immune landscape in these patients, we performed CyTOF analysis on PBMC samples obtained at week 1 (baseline) and week 6 after the beginning of the IL-7 therapy. After stimulation with PMA/Ionomycin, we proceeded to surface and intracellular cytokine staining before acquisition on the CyTOF. The data were then analyzed by expert gating on Cytobank. Results: At 6 weeks post therapy, our data showed an increase in the number of circulating T lymphocytes in the IL-7 cohort, especially CD8 T cells, in accordance with previous literature. Even though of the frequency of CD4 T cells did not increase, the cells showed greater functionalities, with increased expression of IL-2, TNFα and IL-6 upon stimulation by PMA-Ionomycine. Cytotoxic subsets were also positively affected, with increased expression of IFNγ in CD8 T cells, TNFα in NK cells and IL-2 in γδ T cells. Moreover, PD-1 expression was decreased on CD4, CD8 and γδ T cells while CD137 increased on CD4, CD8 and NK cells. In addition, despite a reduction in the pool of circulating monocytes, we observed higher TNFα expression in these cells. Conclusions: Altogether, our data revealed multiple effects of IL-7 in these patients, highlighting a complex set of in vivo mechanisms. In the future, knowledge of these effects may help in choosing the best agents to use in combination with IL-7 and/or the best patients to benefit from IL-7 as part of their therapeutic approach. Trial Registration: NCT01881867 Ethics Approval: The study was last approved by Fred Hutchinson Cancer Research Center Institutional Review Board, IR file 8037, on January 23, 2020